2017
DOI: 10.1038/s41598-017-07805-5
|View full text |Cite
|
Sign up to set email alerts
|

Separate requirements for detection and perceptual stability of motion in interocular suppression

Abstract: In interocular masking, a stimulus presented to one eye (the mask) is made stronger in order to suppress from awareness the target stimulus presented to the other eye. We investigated whether matching the features of the target and the mask would lead to more effective suppression (feature-selective suppression), or not (i.e., non-selective suppression). To control the temporal characteristics of the stimuli, we used a dynamic interocular mask to suppress a moving target, and found that neither matching speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…The results for the main effects and interactions from GLM and Bayes factor are shown in Table 2 and Figure 7 (individual data in Supplementary Figure S6). The faster masks were less effective overall, confirming previous reports (effect #1; Ananyev, Penney, & Hsieh, 2017;Han, Blake, & Alais, 2018). Moving targets had lower contrast thresholds, i.e., were easier to detect, than the stationary target (effect #2).…”
Section: Resultssupporting
confidence: 86%
“…The results for the main effects and interactions from GLM and Bayes factor are shown in Table 2 and Figure 7 (individual data in Supplementary Figure S6). The faster masks were less effective overall, confirming previous reports (effect #1; Ananyev, Penney, & Hsieh, 2017;Han, Blake, & Alais, 2018). Moving targets had lower contrast thresholds, i.e., were easier to detect, than the stationary target (effect #2).…”
Section: Resultssupporting
confidence: 86%
“…Contradictory evidence does exist in the literature, but our view is that in the absence of spatiotemporal control with narrowband stimuli, it is difficult to determine the extent to which feature selectivity influences CFS suppression. For example, Ananyev et al (2017) found that regardless of target speed, slow-moving Mondrian patterns (18/s-28/s) were most effective in suppressing a moving circular disk. Barring more complicated processes, basic spatiotemporal attributes of the stimuli could offer an explanation.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that CFS would involve suppression processes that are selective in the temporal dimension. However, because Mondrian maskers are temporally broadband and CFS studies typically use static targets (but see Ananyev, Penney, & Hsieh, 2017;Kaunitz et al, 2014;Moors et al, 2014), the proposition has not been specifically addressed. In this study, we measured the temporal selectivity of CFS by comparing 2-and 10-Hz narrowband noise maskers on targets modulating at a range of temporal frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the underlying mechanisms of CFS revealed similarities with BR. For instance, rather than a complete and non-selective attenuation, suppression in both paradigms has been shown to be feature-selective for attributes such as orientation (Stuit, Cass, Paffen, & Alais, 2009;Stuit, Paffen, van der Smagt, & Verstraten, 2011;Yang & Blake, 2012; and motion (Stuit et al, 2011;Moors, Wagemans, & de-Wit, 2014; but see Ananyev, Penney & Hsieh, 2017). These featureselective processes also appeared to operate independently.…”
Section: Introductionmentioning
confidence: 99%